Maternal mental health screening and management by health workers in southwestern Uganda: a qualitative analysis of knowledge, practices, and challenges - Gladys Nakidde; Edward Kumakech; John. F. Mugisha (BMC, 2023)
Abstract Background Maternal mental health (MMH) problems, such as perinatal depression, maternal anxiety, suicide ideation and puerperal psychosis among others, have a significant impact on maternal morbidity and mortality, as well as the health and development of children. One in every four pregnant women and one in every five postpartum women in low-income countries, suffer from maternal mental health (MMH) problems. Despite this, MMH screening, diagnosis, and reporting remain scanty in Uganda. Consequently, this study aimed to investigate the knowledge, practices, and impediments that maternity care workers face when screening and managing women with maternal mental health disorders in health facilities in south-western Uganda. Methods In-depth interviews were conducted with 22 health-care professionals who work in maternity care departments in primary and tertiary healthcare facilities in southwestern Uganda to investigate their medical knowledge, clinical practices, and challenges related to the screening and management of maternal mental health problems. Using qualitative content analysis, distinct categories and subcategories were found. Results Medical staff especially midwives lacked specialized training in screening and managing women with maternal mental health problems They screened and managed MMH problems solely based on history and physical examination, and they referred nearly every mother displaying signs of mental illness because they felt ill-prepared to handle them. On the other hand, medical staff with some level of specialized training in mental health particularly staff working in mental health units, were more likely to use a mental health screening tool in addition to history and physical examination; and to treat any women exhibiting signs and symptoms of maternal mental problems without referring them. Lack of in-service training on maternal mental health, poorly coordinated referral systems, reluctance of mentally ill to visit medical facilities, scarcity of mental health specialists, and shortage of relevant medications were identified as the major challenges. Age, experience level, or gender had no effect on screening or management practices. Conclusions The results suggest that specialized training in mental health, and particularly maternal mental health, is essential for the effective screening and management of maternal mental health conditions in South Western Uganda.